On the identity, nomenclatural status and authorship of Coluber monticolus Cantor, 1839 (Reptilia: Serpentes) - Tillack, Frank; Narayanan, Surya; Deepak, V. (Zootaxa, 2021)
Currently, Coluber monticolus Cantor is considered a junior synonym of the Common kukri snake, Oligodon arnensis Shaw. In this work, we analyzed long time disregarded, unpublished original drawings and manuscripts concerning South Asian snakes. Additionally we recall the hitherto little-noticed contact and exchange between B. H. Hodgson and T. E. Cantor. We correct erroneous assumptions regarding the authorship and identity of C. monticolus and, in accordance with Art. 23.9 of the “Code” (ICZN 1999), we declare Dipsas multifasciata Blyth a nomen protectum with priority over Coluber monticolus Hodgson in Cantor (nomen oblitum).